Tracking cancer‐related fatigue during chemotherapy: Insights from a comparative cohort study of early breast cancer patients - Mallard, Joris; Hucteau, Elyse; Schott, Roland; Pivot, Xavier; Pagano, Allan F.; Hureau, Thomas J. (International journal of cancer, 2025)
Cancer‐related fatigue (CRF) is a multifactorial symptom commonly experienced by breast cancer patients treated with chemotherapy (CT) that impairs quality of life and may influence cancer recurrence by reducing treatment compliance. This cohort study examined the kinetics of CRF throughout CT in breast cancer patients and determined its relationship with exercise‐related variables. One hundred breast cancer patients were included. Three time points were investigated: pre‐CT, 8 weeks, and post‐CT. Patients were categorized as fatigued or non‐fatigued according to their FACIT‐F score. Exercise capacity (assessed using the 6‐minute walking test), muscle mass and force, neuromuscular fatigue, and physical activity level were measured. Among the seven patterns of CRF trajectories identified, three represented 78% of the fatigued patients. Fatigued patients exhibited reduced exercise capacity compared to non‐fatigued patients during CT (p = 0.001). This was associated with greater knee extensor (p < 0.001) and handgrip (p = 0.009) neuromuscular fatigue and lower physical activity level (p < 0.001) in fatigued patients. The model combining knee extensors neuromuscular fatigue (p = 0.007) and force (p = 0.081), 6‐minute walking test distance (p < 0.001) and physical activity level (p = 0.029) explained 39% of the variance in the FACIT‐F score evolution from pre‐ to post‐CT. The dissociation between fatigued versus non‐fatigued patients highlighted that CRF was associated with altered exercise capacity and neuromuscular fatigue. Exercise‐related variables seem to play an important role in CRF evolution during CT, suggesting that exercise training should be initiated at the start of CT. What's New? Cancer‐related fatigue is a multifactorial symptom commonly experienced by breast cancer patients treated with chemotherapy. Here, the authors investigated the temporal associations between cancer‐related fatigue and exercise capacity to better tailor exercise interventions during chemotherapy. The cohort study identified seven cancer‐related fatigue trajectories, with three of them experienced by 78% of patients. Cancer‐related fatigue was associated with reduced exercise capacity, neuromuscular fatigue, and lower physical activity level. One model based on four exercise‐related parameters explained 39% of the variance in cancer‐related fatigue evolution, emphasizing the need for early exercise interventions prioritizing both exercise capacity and neuromuscular force.